Glanvill after Glanvill - Tullis, S; Tullis, Sarah (2008)
﻿ This thesis provides a new consideration of the late twelfth-century legal treatise commonly known as Glanvill. Detailed analysis of the extant Glanvill manuscripts has enabled a number of important new conclusions about the nature of the treatise itself and its textual history and development over time relative to the changing common law. The function and ongoing usage of the treatise are discussed in detail and conclusions are drawn about how, when and why the treatise continued to be copied and/or engaged with and what this may reveal about the history of the English common law. Some traditional views about the treatise and its textual history have been challenged, not least the general perception of its two textual traditions as monolithic. This study adds substantively to the scholarship on the two so-called 'versions' of the treatise, Glanvill Continued and Glanvill Revised, both of which have been reassessed. The traditional view that Glanvill Continued represented a significant and 'official' attempt at modernizing the treatise for a mid thirteenth-century audience has been challenged. In contrast, new study of the nature and text of Glanvill Revised has re-emphasized its importance in the treatise's history and the uniqueness of its bipartite revision and re-revision, differentiating and describing these clearly for the first time. An attempt has also been made to see the treatise in the context of the later legal literature that followed it and to link such literature back to Glanvill. It is suggested that the explosion of English legal literature in the thirteenth century at once represents the treatise's success as the written starting point of the common law and its failure, given that, with the notable exception of Bracton, such literature moves substantively away from the earlier treatise. Having said this, Glanvill arguably continued to play a role, direct and indirect, through the later literature of the law and continued to be copied, read and used alongside it. More systematic study has been undertaken of the Scottish text based upon Glanvill, the Regiam Majestatem, and it is argued that the Regiam is a much more genuine attempt at re-editing Glanvill than has traditionally been thought and that the twelfth-century English treatise may have been surprisingly applicable in early fourteenth-century Scotland. Finally, this study has involved a new assessment of the later history of Glanvill from the fifteenth century to today, considering both the later ownership and use of its manuscripts and early printed editions and its legal and political citations. Consideration of the varying function and usage of the treatise over time enables light to be thrown upon Glanvill, the later periods in which it was read and used and the beginnings of legal history.